Robert Winters: A Nova Scotia Liberal in National Politics - Cahill, Barry (Journal of the Royal Nova Scotia Historical Society, 2022)
The subject of this article is the federal Liberal politician who became one of Canada’s biggest businessmen of the 1960s, only to renounce it to return to politics. Twice an MP and twice a Cabinet minister, Robert Winters (1910–1969) failed, by a mere 249 votes, to defeat Pierre Trudeau at the Liberal leadership convention in April 1968. As such, he is an exceptional “might-have-been” of Canadian political history. Had he succeeded, he would have been the first Liberal prime minister from Atlantic Canada, and the first business executive to become leader of the Liberal Party. Despite his prominence and importance, little of substance has been written about Winters.